Pengaruh Panjang Serat terhadap Kekuatan Tarik Fiber Metal Laminate Composite - Hanif Arsalan Dani Subekti; Hilmi Iman Firmansyah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to evaluate the effect of ramie fiber length on the tensile strength of Fiber Metal Laminate (FML) hybrid composites. The background of this research is the saturation with the use of synthetic composite materials, which encourages the search for renewable materials to replace synthetic fibers. In this study, ramie fibers were immersed in a 6% NaOH solution before use, and the composite manufacturing process was carried out using the hand lay-up method. Annealed Aluminum 1100 was used as the laminating layer. The results of the study showed that the highest tensile strength was obtained in composites with a ramie fiber length of 5 cm, with a tensile strength of approximately 105 MPa. These findings indicate the potential of using ramie fibers as a sustainable and efficient alternative in FML hybrid composite applications.